Age-related changes in physical and perceptual markers of recovery following high-intensity interval cycle exercise - Borges, N.; Reaburn, P.; Doering, T. M.; Argus, C.; Driller, M. W. (Experimental Aging Research, 2018)
The purpose of this study was to compare physical performance, perceptual and haematological markers of recovery in well-trained masters and young cyclists across 48 h following a bout of repeated high-intensity interval exercise. Methods: Nine masters (mean ± SD; age = 55.6 ± 5.0 years) and eight young (age = 25.9 ± 3.0 years) cyclists performed a high-intensity interval exercise session consisting of 6 × 30 s intervals at 175% peak power output with 4.5 min rest between efforts. Maximal voluntary contraction (MVC), 10 s sprint (10SST), 30-min time trial (30TT) performance, creatine kinase concentration (CK) and perceptual measures of motivation, total recovery, fatigue and muscle soreness were collected at baseline and at standardised time points across the 48 h recovery period. Results: No significant group-time interactions were observed for performance of MVC, 10SST, 30TT and CK (P > 0.05). A significant reduction in 10SST peak power was found in both masters (P = 0.002) and young (P = 0.003) cyclists at 1 h post exercise, however, both groups physically recovered at similar rates. Neither group showed significant (P > 0.05) or practically meaningful increases in CK (%? < 10%). A significant age-related difference was found for perceptual fatigue (P = 0.01) and analysis of effect size (ES) showed that perceptual recovery was delayed with masters cyclists reporting lower motivation (ES ±90%CI = 0.69 ± 0.77, moderate), greater fatigue (ES = 0.75 ± 0.93, moderate) and muscle soreness (ES = 0.61 ± 0.70, moderate) after 48 h of recovery. Conclusion: The delay in perceived recovery may have negative effects on long-term participation to systematic training.